Pendidikan Agama Islam Berwawasan Lingkungan di Sekolah Menengah Atas: Environmentally-conscious Islamic Education in Senior High School - Asep Rahmatullah (AJMIE: Alhikam Journal of Multidisciplinary Islamic Education, 2026)
Environmentally-conscious Islamic Education at SMA Plus 30 Juz, Serang, Banten, serves as a relevant case study to address the challenges of the ecological crisis while optimizing the role of Islam in building environmental awareness. This qualitative research aims to examine in-depth the implementation, value construction, and internalization of Islamic education integrated with ecological awareness at the school. The results show that the holistic integration of Islamic values ​​(such as the concept of caliph, trust, and morals) with environmental education operationalized through a contextual curriculum, participatory learning methods, and school-based programs successfully created a transformative educational ecosystem. Collaborative strategies between teachers, students, and all stakeholders, supported by school policies, not only enrich theoretical religious understanding but also internalize it into concrete behaviors such as waste management, hydroponics, and energy saving